V37. Interactions between primary and secondary motor areas for recovered hand functions after stroke. Issue 8 (August 2015) - Zimerman, M.; Weide, S.; Wessel, M.; Schulz, R.; Timmermann, J.E.; Bönstrup, M.; Morishita, T.; Koch, P.; Gerloff, C.; Hummel, F.C.
<x xml:space="preserve">Abstract</x> Objectives Goal oriented hand movements are the final product of complex interplay between multiple cortical regions of the frontoparietal cortex. Following stroke, recovery of function might be related to structural and functional modifications in the surviving brain networks. Strikingly, the ventral premotor cortex (PMv) plays a crucial role in the sensorimotor processing engaged in shaping finger movements and shares extensive reciprocal projections to the primary motor cortex (M1), making the PMv a promising structure involved in hand motor recovery after stroke. By instance, mapping studies in stroke animal models consistently showed that improvement in forelimb motor performance was associated with reorganization within the PMv. However, precise functional interactions between the PMv and the M1 in the process of hand motor recovery have not been investigated in stroke patients. Paired-pulse transcranial magnetic stimulation (pp-TMS) was used in order to evaluate PMv-M1 interactions in stroke patients and healthy controls. To further disentangle whether recovery-related changes are specific to PMv-M1 or apparent in all interactions between primary and secondary motor areas after stroke, connectivity between posterior parietal cortex (PPC) and M1 have been also assessed. Methods 22 patients (aged 62.3 ± 9.8 SD) with mild to severe unilateral hand motor deficit and 20 healthy controls (aged 59.7 ± 20.9 SD) participated in the present study. Within experiment-1, PMv-M1 interactions were investigated by using neuronavigated-ppTMS in both the affected and unaffected hemisphere, considering 6 interstimulus intervals (ISI; 2, 4, 6, 8, 10 and 15 ms) between conditioning and test pulse. In experiment-2, PPC-M1 interactions were investigated targeting two PPC regions: the anterior intraparietal sulcus (aIPS) and the caudal intraparietal sulcus (cIPS). Results Experiment-1: A consistent difference between patients and controls, with a group by ISI interaction, has been observed for both the affected (F = 14.9, p < 0.001) as well as the unaffected (F = 5.3, p < 0.001) hemisphere. Further posthoc analysis confirmed a significant difference at 6 and 8 ms between both groups (ISI6 ms = T = 3.4, p = 0.002; ISI8 ms = T = 7.1, p < 0.001), with consistent facilitation in stroke and rather inhibition in healthy controls. Interestingly, the amount of facilitation observed at 8 ms in stroke patients was positively correlated with the level of force production of the paretic hand (R2 = 0.33, p = 0.010) assessed by the laterality-index of grip-force. Experiment-2: No group differences have been observed between aiPS-M1 and cIPS-M1 in both hemispheres. Conclusions The present pp-TMS approach enabled us to assess in vivo the specific contributions of individual brain areas to recovery of function after stroke. These findings demonstrate changes in interareal connectivity between the PMv and the M1 associated with recovered hand motor function. These data support a paramount role of the PMv within the process of functional reorganization and successful hand motor recovery, as suggested in previous animal work, contributing significantly to the understanding of the mechanisms underlying cortical reorganization after focal brain lesions.